TINGKAT PENGETAHUAN IBU HAMIL BERHUBUNGAN DENGAN KONSUMSI TABLET TAMBAH DARAH - Nuraliyah Sugianti; Septy Ariani; Sarmila (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
Anemia is a major nutritional problem in Indonesia, especially iron deficiency anemia. Anemia has a serious impact on pregnant women. The impact on the mother and fetus is the occurrence of wrinkles, bleeding during pregnancy, premature labor, disturbances to the fetus, labor and puerperal disorders. It is very important to overcome anemia in pregnant women, one of which is by taking Blood Supplement Tablets. There are many factors that can affect pregnant women in consuming Blood Supplement Tablets, one of which is the level of knowledge of pregnant women. The purpose of this study was to determine the relationship between the level of knowledge of pregnant women and the consumption of iron tablets. This study used quantitative methods, population and sample of 106 pregnant women using total sampling. The results showed that pregnant women who had good knowledge were 71 people (67.0%), moderate knowledge were 26 people (24.5%), knowledge was lacking as many as 9 people (8.5%) with a p value of 0.00. It can be interpreted that the level of knowledge of pregnant women is related to the consumption of iron tablets.